2019
DOI: 10.1101/575290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MTH1 promotes mitotic progression to avoid oxidative DNA damage in cancer cells

Abstract: BACKGROUND: We developed MTH1 inhibitors (MTH1i) TH588 and TH1579 showing broad anti-cancer activity, while structurally distinct MTH1i fail to kill cancer cells. Here, we describe a new role of MTH1 in mitosis and the detailed mechanism of action of TH1579 (karonudib) and other structurally distinct MTH1i. MATERIALS AND METHODS: Cancer cell lines or zebrafish embryos were treated with MTH1i or siRNA targeting MTH1 and analysed primarily by live cell and immunofluorescence microscopy, survival assays, DNA fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells. Some MTH1 inhibitors, such as TH588 and TH1579, could block the interaction of MTH1–tubulin, therefore inducing the mitotic arrest of cancer cells 49 . Taken together, the redox balance of the cellular processes involving oxidative metabolism and elimination, the tumorigenic models, off-target possibility and so on, might directly or indirectly determine the outcome of MTH1 inhibitors, complicating it as a viable therapeutic approach for cancer eradication by inhibiting MTH1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells. Some MTH1 inhibitors, such as TH588 and TH1579, could block the interaction of MTH1–tubulin, therefore inducing the mitotic arrest of cancer cells 49 . Taken together, the redox balance of the cellular processes involving oxidative metabolism and elimination, the tumorigenic models, off-target possibility and so on, might directly or indirectly determine the outcome of MTH1 inhibitors, complicating it as a viable therapeutic approach for cancer eradication by inhibiting MTH1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show on one hand that MTH1 is an important target for cancer [14,15,37], whereas on the other hand some studies claim MTH1 inhibition to be nontoxic, thereby questioning the anticancer therapeutic potential of MTH1i [38,39]. We reported that mitotic arrest, elevated ROS and 8-oxodGTP are important for the efficacy of TH1579 and that noncytotoxic MTH1i can show synergistic effects when combined with mitotic arrest agents [40]. Emerging evidence connect mitotic arrest with ROS.…”
Section: Discussionmentioning
confidence: 86%
“…Here, we demonstrated that all B-cell lymphoma cell lines displayed a pronounced mitotic arrest in response to karonudib treatment, due to aberrant mitotic spindle formation. This may be related to the mechanism of action of karonudib, targeting microtubuli 13 . The transcriptional changes induced by karonudib in lymphoma cell lines supports this hypothesis as the only significant enrichment profiles identified were "spindle formation" and "G 2 /M-arrest".…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts cancer cells which frequently upregulate MTH1 to compensate for increased ROS with corresponding higher oxidized nucleotide levels 11 , 12 . Furthermore, karonudib has a dual mechanism as it also directly and indirectly can perturb microtubule polymerization dynamics via an emerging role of MTH1 in mitosis 13 , 14 . Inhibition of MTH1 has potent anti-tumor activity in mouse models of colon cancer, malignant melanoma, hepatocellular carcinoma, -lung- and breast cancer 5 , 15 18 .…”
Section: Introductionmentioning
confidence: 99%